IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE IN VILLAGE FINANCIAL MANAGEMENT: A CASE STUDY OF BUMDES GIRI AMERTHA SADHU BONTIHING VILLAGE - Aryanta, I Gede Agas; Wahyuni, Made Arie (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to analyze the implementation of Good Corporate Governance (GCG) principles in Giri Amertha Sadhu Village-Owned Enterprises (BUMDes) in Bontihing. The GCG principles studied include transparency, accountability, responsibility, independence, and fairness. This study uses a qualitative approach with observation, interview, and documentation methods. The results of the study indicate that the implementation of the principles of transparency and accountability is still relatively weak compared to other aspects. Financial information has not been conveyed openly to the public, and activity reporting has not been carried out routinely and on time. On the other hand, the principle of responsibility has been implemented quite well through the involvement of administrators in responding to community aspirations and village deliberation forums. Based on these findings, it is recommended that BUMDes increase transparency through easily accessible publication media and build a more regular reporting system to strengthen accountability. This study is expected to be used as evaluation material in improving BUMDes governance to be more professional and sustainable.